HGG-33. PATIENT DERIVED CELL LINES TO STUDY ATRX AND ALT IN PEDIATRIC BRAIN TUMORS. Issue 2 (22nd June 2018) - Ijaz, Heba; Dilley, Robert; Koptra, Mateusz; Garcia, Gonzalo; Zhu, Yuankun; Zhang, Bo; Baubet, Valerie; Mason, Jennifer; Resnick, Adam; Gaonkar, Krutika; Waanders, Angela; Raman, Pichai; et al.
Abstract: BACKGROUND: All cancers acquire a mechanism of telomere maintenance (TMM) for genomic stability and unlimited replicative potential. Some cancers, including a subset of pediatric brain tumors, use the TMM of alternative lengthening of telomeres (ALT). However, there are few cancer cell lines with ALT, representing a mixture of histotypes. We aim to generate patient derived pediatric brain tumor cell lines with and without ALT for downstream analyses. METHODS: The Children's Brain Tumor Tissue Consortium (CBTTC) database was queried for pediatric brain tumor types likely to have ALT and tumor in freezing media. Patient derived cell lines were generated as adherent and suspension lines. Corresponding primary tumor samples were analyzed for ALT by c-circle assay (CCA) and WGS for targeted gene mutations and estimated telomere length. RESULTS: 38 high-grade glioma and PNET samples were processed into patient derived cell lines. To date, at least one line from 25 of the 38 tumors are growing well in various stages of development and validation, with 10 having the expected somatic mutations, including 3 with ALT. Analysis of the cell lines corresponding primary tumor revealed that 13/37 (35%) are ALT (CCA) positive. Targeted H3.3 sequencing showed that 3/3 (100%) of G34R mutant, 3/8 (37%) of K27M mutant and 7/26 (27%) of H3.3 wild-type tumors are ALT positive. WGS was available for 29 tumors, including 10 with ALT. The ALT positive tumors have damaging mutations in TP53 (6/10), ATRX (6/10), H3.3 (6/10) and IDH1 (1/10) and are computationally predicted to have long telomeres (p=0.03).